Does high-grade dysplasia/carcinoma in situ of the biliary duct margin affect the prognosis of extrahepatic cholangiocarcinoma? A meta-analysis - Ke, Qiao (World J Surg Oncol, 2019)
BACKGROUND: High-grade dysplasia/carcinoma in situ (HGD/CIS) of the biliary duct margin was found to not affect the prognosis of patients with extrahepatic cholangiocarcinoma by recent studies, but it has not yet reached a conclusion. METHODS: Eligible studies were searched by PubMed, PMC, MedLine, Embase, the Cochrane Library, and Web of Science, from Jan. 1, 2000 to Jun. 30, 2019, investigating the influences of surgical margin status of biliary duct on the prognosis of patients with resectable extrahepatic cholangiocarcinoma. Overall survival (OS) and local recurrence were evaluated by odds ratio (OR) with 95% confidence interval (CI). RESULTS: A total of 11 studies were enrolled in this meta-analysis, including 1734 patients in the R0 group, 194 patients in the HGD/CIS group, and 229 patients in the invasive carcinoma (INV) group. The pooled OR for the 1-, 2-, and 3-year OS rate between HGD/CIS group and R0 group was 0.98 (95% CI 0.65~1.50), 1.01 (95% CI 0.73~1.41), and 0.98 (95% CI 0.72~1.34), respectively. The pooled OR for the 1-, 2-, and 3-year OS rate between HGD/CIS group and INV group was 1.83 (95% CI 1.09~3.06), 4.52 (95% CI 2.20~9.26), and 3.74 (95% CI 2.34~5.96), respectively. Subgroup analysis of extrahepatic cholangiocarcinoma at early stage showed that the pooled OR for the 1-, 2-, and 3-year OS rate between HGD/CIS group and R0 group was 0.54 (95% CI 0.21~1.36), 0.75 (95% CI 0.35~1.58), and 0.74 (95% CI 0.40~1.37), respectively, and the pooled OR for the 1-, 2-, and 3-year OS rate between HGD/CIS group and INV group was 3.47 (95% CI 1.09~11.02), 9.12 (95% CI 2.98~27.93), and 9.17 (95% CI 2.95~28.55), respectively. However, the pooled OR for the incidence of local recurrence between HGD/CIS group and R0 group was 3.54 (95% CI 1.66~7.53), and the pooled OR for the incidence of local recurrence between HGD/CIS group and INV group was 0.93 (95% CI 0.50~1.74). CONCLUSION: With the current data, we concluded that HGD/CIS would increase the risk of local recurrence compared with R0, although it did not affect the prognosis of patients with extrahepatic cholangiocarcinoma regardless of TNM stage. However, the conclusion needs to be furtherly confirmed.